PENGARUH MEDIA COLOUR CORRUGATED PAPER TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK IT AL-KAHFI INDRALAYA - Putri, Sabrina Amanda; Yin Yin Septiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of colour corrugated paper media on the fine motor skills of children aged 5-6 years at TK IT Al-Kahfi Indralaya. The research method used in this study is a quantitative Pre-experimental method with a one-shot case study design. While the data collection technique uses observation (Checklist sheet). The sample selection in this study used a cluster random sampling technique, namely 16 children aged 5-6 years consisting of 6 boys and 10 girls. The results of data analysis on the normality test that has been carried out show that the data is normally distributed because x² count ≤ x² table, namely x² count = 1.38 and x² table = 24.96 then from the t-test calculation it is obtained that t count = 5.01 and t table = 1.753. This shows that Ha is accepted and Ho is rejected, namely t count ≥ t table (5.01 ≥ 1.753). Therefore, the test results can be concluded that colour corrugated paper media has an effect on the fine motor skills of 5-6 year old children at Tk IT Al-Kahfi Indralaya.